A REVIEW ON PHYTOCHEMICALS AND PHARMACOLOGICAL CHEMICALS OF DATE PALM (PHOENIX DACTYLIFERA) - Mehdi Shah, Syed Mosyab; Abbas Naqvi, Summar; Jafar Jaskani, Muhammad; Mehdi Shah, Irtaza (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2023)
Date palm (Phoenix dactylifera L.) is widely cultivated fruit tree having thousands of years of usage as food and medicinal plant. Its fruits, trunk and leaves contain a diverse array of phytochemicals with potential pharmacological activities. In recent years, the application of phytochemicals and biological active compounds, present in date palm, is getting attention of scientist to explore their role in the betterment of humans under malnutrition circumstances. The present review summarizes the current state of information on the phytochemicals and pharmacological activities of date palm tree. Phytochemicals found in date palm include polyphenols, flavonoids, carotenoids, tocopherols and triterpenoids. These compounds have been revealed with a wide range of anti-oxidant, anti-inflammatory, including biological activities and anti-tumor activities. Additionally, date palm has been found to have antidiabetic, hypolipidemic, and neuroprotective effects. These chemicals are also found affective against various diseases including cancer, cardiovascular issues and diabetes. These compounds have also been exposed to have cholesterol lowering anti-tumor effect and anti-inflammatory. In addition, the leaves of the date palm contain tannins, which have been found to have antimicrobial and antioxidant activities. The date palm’s fruit contains various bioactive compounds, including dietary fiber, vitamins, phenolic and minerals compounds. These compounds have been shown to have a range of health benefits, including improving gut health, reducing the stress of oxidative, and reducing the cardiovascular disease risk. Additionally, the fruit of the date palm has been found to have prebiotic effects, promoting the growth of beneficial gut bacteria.